PEMBENTUKAN KARAKTER PRIBADI PESERTA DIDIK MELALUI PENGGALIAN NILAI PADA PELAJARAN DI SEKOLAH DASAR - Maskhur, . (Forum Tarbiyah, 2011)
Abstract: Educational materials that span the ‘hierarchy in varioussubjects in elementary school, as well as local curriculum materials,can serve as an instrument for the formation of the character ofstudents. Therefore, the formation of character typology can beinfluenced by external and internal factors, both tangible educational,environmental, genetic and gene stimulation as well as ways ofthinking. In essence, every subject, including lessons in primaryschools never be separated from values, both aesthetic values, ethics,fairness doctrine, fairness, freedom and order, equality, harmony,solidarity, courage, love of peace, discipline, loyalty , empathy andothers. Since all the real subject matter is never value-free and thematerials are very influential on the character formation of students,then the extortion to the values contained in it are things that mustbe done for the later revealed and transmitted to students. The processof internalization of proficiency level, into the private learners, can bedone by means of analysis and clarification of values for habituationvalues contained in the elementary school subjects.